Implications Status Alteration and Nāẓir Position on Wealth Endowments Producivity - Fikfik Taufik (International Journal of Nusantara Islam, 2017)
Endowments are Aaliyah worship which has the noble social function to comply the various things that are relating the physical requirement and spiritual of society. To create the social function, there was appointed person or group of people, and on behalf of the individuals or legal entity optimally in charge of managing the endowments property. The endowment is an Islamic legal institution which was legality is based on the Qur’an and Hadith. In addition, regarding the lawmaking of endowments are also sourced from ijtihad, which focuses on mashed terms of shari'a, those are for creating the beneficence and strange on damage. Nāẓir alteration has to own the legality either form fiqh consideration (jurisprudence) or legislation and also have to be considered how far the conformity of alteration practice with fiqh (jurisprudence) and legislation, The alteration Nāẓir endowments as one of the efforts to optimize the wealth endowments management it's needed to be examined further. On this observation, it is used a qualitative approach with the research resources (research library), and in-depth interviews. The normative data which constituting a fact on the ground that has been collected then analyzed and also compared. This observation results explained that the alteration of Nāẓir endowments also has the legality, either fiqh (jurisprudence) or the legislation. The implementation of its changes is also implicated on optimizing the endowments property management, both in terms of results, or in terms of management.